Collaborative Writing and the Poetics of the Occasion: The Pandemic Sonnets of Cindy Tran and Craig Santos Perez - Laura T. Smith (Angles)
During the early months of the COVID pandemic in 2020, writers turned to the practice of sonnet-writing to connect with others, stem isolation, and take stock of the multiple crises presented by the pandemic and its complex social contexts. This essay examines two collaboratively written pandemic sonnet projects, The Poetry Society of New York’s May Day 2020 crown and Cindy Tran’s Sonnet Crown for NYC, along with the pandemic eco-sonnets of Craig Santos Perez. These pandemic sonnets articulate our complexly connected identities while highlighting the pandemic sonnet’s capacities for meditating on and interrogating our expanding webs of connection. As collaborative writing projects and works of occasional poetry, these pandemic sonnet projects reposition the sonnet in contemporary American poetics as a social and socially-embedded practice, linking contemporary sonnet practice to the highly social poetic exchanges associated with the sonnet from its earliest roots.